Analisis Hadis-Hadis tentang Taat Kepada Pemimpin Implikasi dalam Kehidupan Bernegara - Asep Saepudin (Jurnal Ilmu Sosial dan Humaniora, 2024)
God commands man to fulfill what He commands and to stay away from what is forbidden. Among God's commandments is to listen to and obey leaders. Obedience to leaders is a religious command that has an impact on increasing the country's political stability. There are many hadiths that explain the obligation to obey a leader. However, many Muslims do not know and study these hadiths. So it is interesting for researchers to discuss it. By using literature research methods, as well as the use of approaches tailored to the main objectives of the research, researchers want to discuss it in more detail. The researcher also limits himself to the hadiths narrated by Bukhori and Muslims. The results of this research are: 1) Hadith About Obedience to Leaders Even If Your Back Is Beaten and Property Is Confiscated) Hadith About Obedience to Leaders in All Circumstances 3) Hadith Obedience to Leaders is Obedience to Allah 4) Hadith Fulfills Obligations That Become the Right of Leaders and Asks Allah for Our Rights That Are the Obligations of Leaders 5) Hadiths of Obedience to Leaders Except in Disobedience